SC and Maintenance Diagnosis Versus Excellency - Jellouli Olfa; Bettaieb Alaa (International Journal of Supply Chain Management, 2022)
Challenging the management or logistics of a system is an ongoing process within the PDCA framework. The problem that remains is which diagnosis to choose. It is in this context that my article is situated. Indeed, it develops a diagnosis of the supply chain of a transport company as well as a diagnosis of the maintenance of the latter aiming for excellency in industrial management.